Legal and Constitutional Guarantees for Freedom of Expression in Iraq in the Age of Digital Media - Badai, Abdullah (Journal of Legal Sciences, 2026)
Freedom of expression is one of the most important freedoms, and many other freedoms are linked to it. Therefore, it has been enshrined in various international human rights treaties, in addition to being stipulated in all constitutions at the international and national levels. Therefore, this research sheds light on the legal and constitutional guarantees for freedom of expression in Iraq in the age of digital media. In our research, we relied on the use of the analytical-descriptive approach, and through our research, we concluded that the Iraqi constitution recognizes freedom of expression as a guaranteed right. However, the activation of this right in practical reality still faces legal and executive challenges. The absence of a comprehensive digital media law that is compatible with the changes occurring in the structure of the media and social media has led to contradictions in implementation and legal gaps. We therefore recommend the need to work toward issuing a modern national law on freedom of expression and digital media that respects human rights, aligns with international standards, and includes clear guarantees for freedom of expression online.